Study for the diagnostic screening of paroxsymal nocturnal hemoglobinuria in Turkey: Prospective multicentric evaluation of suspected patients. (October 2019) - Ilhan, Osman; Ozdemir, Zehra Narli; Ozet, Gulsum; Falay, Mesude; Yenerel, Mustafa; Tuglular, Tulin; Turgut, Mehmet; Guvenc, Birol; Unal, Ali; Ayyıldız, Orhan; Andic, Neslihan; Hacıhanefioglu, Abdullah; et al.
Abstract: Background: Paroxysmal nocturnal hemoglobinuria (PNH) is a rare disease presenting with variable and various clinical findings. PNH might be overlooked and diagnosis may be delayed due to low awareness about PNH. This is the first multicenter study in Turkey, investigating the efficiency of diagnostic screening of PNH by multiparameter flow cytometry (FCM) according to consensus guidelines. Methods: We evaluate the efficiency of consensus clinical indications for PNH testing with FCM in 1689peripheral blood samples from 20 centers between January 2014 and December 2017. Results: Overall, at the 20 centers contributing to this study, PNH clone were detected in 62/1689 samples (3.6%) by FCM test. 75.8% (n = 47) of patients with PNH clone had aplastic anemia, 3.2% (n = 2) had Coombs (-) hemolytic anemia, 6.5% (n = 4) had unexplained cytopenia, 3.2% (n = 2) had MDS with refractory anemia, 1.6% (n = 1) had hemoglobinuria and 9.7% (n = 6) had others (elevated LDH, splenomegaly, etc.). In contrast, we detect no PNH clone test in patients who were screened for unexplained thrombosis. Conclusions: Our study showed that current clinical indications for PNH testing are highly efficient and diagnostic screening of suspected patients for PNH with FCM is recommended. However, advanced screening algorithms are required for patients presenting with unexplained thrombosis and normal complete blood count.